The Effect Of Information Technology Use And Internal Control On The Quality Of Financial Reports Of The Government Of Aceh Barat Daya Regency - Aula Ulpika (Jurnal Multidisiplin Sahombu, 2024)
Study This aiming For know influence utilization technology information and internal control over quality report finance government in Southwest Aceh Regency . Population in the study This as many as 39 SKPK with Number of research samples This is 76 respondents with method purposive sampling with criteria head subsection finance , treasurer reception and treasurer expenditure with a minimum work period of 2 years . Data used is the primary data collected through questionnaire . Data analysis using analysis multiple linear regression ) with IBM SPSS version 30. The results of the study This show that utilization technology information and internal control have an impact positive to quality report finance Government Southwest Aceh Regency .